Biases in international portfolio allocation and investor protection standards - Kwabi, Frank O.; Thapa, Chandra; Paudyal, Krishna; Adegbite, Emmanuel (Elsevier, 2017)
Economic reasoning suggests that financial globalization that encourages optimal international portfolio investments should improve investor protection standards (IPS) of a country. In practice, however, investors manifest varying degrees of suboptimal international portfolio allocations. Using a panel dataset covering 44 countries spanning over 15 years we examine whether suboptimal equity portfolio allocation in part is associated with the cross-country variations in IPS. Consistent with economic reasoning we find robust indications that international portfolio allocation may play an important role in the development of IPS. More specifically, the quality of IPS improves with higher degrees of optimal international equity portfolio allocation of domestic and foreign investors.